Problematika Pendidikan Inklusi di SMAN 4 Kota Jambi dalam Perspektif Filsafat Pendidikan: Problems of Inclusive Education at SMAN 4 Jambi City from the Perspective of Educational Philosophy - Lega Anattri; Rayandra Asyhar; Asrial Asrial; Syaiful Syaiful; Revis Asra; Tedjo Sukmono (Undiksha, 2026)
Inclusive education is an educational paradigm that places all students as individuals who have equal rights, dignity, and learning opportunities without differentiating physical, intellectual, social, and cultural conditions. From the perspective of educational philosophy, inclusive education is not only interpreted as a policy of accepting children with special needs (ABK) in general schools, but as an effort to build a humanistic, democratic, and equitable education system through respect for human diversity. This study aims to analyze the problems of inclusive education at SMAN 4 Jambi City from the perspective of educational philosophy. The novelty of this research lies in the philosophical analysis of inclusive education through ontological, epistemological, and axiological dimensions at the high school level, which has so far been studied more from the aspects of policy and implementation. The state of the art of previous research focuses on inclusive education management, teacher competence, and adaptive learning, while the research gap of this study shows the limited study of inclusive education philosophy that integrates aspects of student existence, construction of learning knowledge, and human values ​​in the practice of inclusive education. This research employed a qualitative research method with a case study approach. Data collection included observation, in-depth interviews, and documentation, followed by data